Effectiveness of Psychotherapy on Quality of Life People with HIV/AIDS - Armunanto, Anung Widi; Yona, Sri (STIKep PPNI Jawa Barat, 2024)
Aims: patients with HIV/AIDS have unique challenges regarding their quality of life, with factors such as physical symptoms, use of antiretroviral therapy, social support, and psychiatric conditions being important determinants. Method: This study is a systematic literature study. Literature search through online databases ProQuest, Scopus, Google Scholar, PubMed. The keywords used were: plwh, hiv aids, hiv positive, hiv patient, psychotherapy, cbt, mindfulness, counselling, quality of life, qol, depression, stress, with Bolean logic AND and OR. Journal of the last 10 years (2013-2023), using English, is a journal article, open access, involving adult respondents, full text, HIV/AIDS, adult, clinical trial, RCT. Exclusion criteria: Encyclopedia article, book chapter, conference, correspondent, editorial, news, practice guideline, protocol, systematic review, literature review and meta-analysis qualitative study. Screening and selection of articles are displayed in the PRISMA diagram. Selected articles were subjected to critical appraisal of RCT studies. Results: 7 articles met the criteria and were discussed in this study. 5 articles used CBT intervention and 2 used ITP intervention. Both CBT and ITP proved to have significant results in improving the quality of life of PLWHA. Conclusions: Psychotherapy, especially CBT and ITP, has a significant impact on the quality of life of people living with HIV. Integration of care, especially for alcohol use disorders, and utilization of telemedicine technologies, such as tele-IPT, also provide feasible solutions to improve accessibility of care, especially in rural areas.